2017
DOI: 10.1007/s10266-017-0324-3
|View full text |Cite
|
Sign up to set email alerts
|

Bonding performance of self-adhesive flowable composites to enamel, dentin and a nano-hybrid composite

Abstract: This study aimed to analyze bond strengths of self-adhesive flowable composites on enamel, dentin and nano-hybrid composite. Enamel, dentin and nano-hybrid composite (Venus Diamond, Heraeus Kulzer, Germany) specimens were prepared. Three self-adhesive composites (Constic, DMG, Germany; Fusio Liquid Dentin, Pentron Clinical, USA; Vertise Flow, Kerr Dental, Italy) or a conventional flowable composite (Venus Diamond Flow, Heraeus Kulzer, Germany, etch&rinse technique) were applied to enamel and dentin. Nano-hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 32 publications
5
51
0
4
Order By: Relevance
“…Self‐adhesive composites combine the benefits of adhesive and composite technology, bringing novel horizons to restorative techniques, as they are claimed to bond to tooth tissue without a separate adhesive . These materials contain self‐etching and/ or self‐adhesive monomers that are able to etch enamel and dentin surfaces or chemically bond to hydroxyapatite, such as the 4‐methacryloxyethyl trimellitic acid, glycerol phosphate dimethacrylate monomers, 10‐MDP monomer, and so on . Though several in vitro studies on physical properties, bond strength, and marginal sealing potential have been published, clinical research studies ongoing on these products are still limited .…”
Section: Composite System Classification Of Dental Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Self‐adhesive composites combine the benefits of adhesive and composite technology, bringing novel horizons to restorative techniques, as they are claimed to bond to tooth tissue without a separate adhesive . These materials contain self‐etching and/ or self‐adhesive monomers that are able to etch enamel and dentin surfaces or chemically bond to hydroxyapatite, such as the 4‐methacryloxyethyl trimellitic acid, glycerol phosphate dimethacrylate monomers, 10‐MDP monomer, and so on . Though several in vitro studies on physical properties, bond strength, and marginal sealing potential have been published, clinical research studies ongoing on these products are still limited .…”
Section: Composite System Classification Of Dental Compositesmentioning
confidence: 99%
“…33,37 These laboratory studies revealed that there are still many controversies about bonding effectiveness and mechanical properties so far, and some studies reported that self-adhesive composites show limited interaction with dentin or enamel. 33,38 Consequently, critical investigation and clinical assessments are needed for self-adhesive composites.…”
Section: Compomers (Polyacid Modified Resin Composites)mentioning
confidence: 99%
“…Each dental adhesive comprises a specific functional monomer that determines its adhesive performance to dental tissue [24]. Vertise TM Flow contains GPDM monomers which are well-known from the OptiBond FL adhesive system [25]. GPDM features a rather short spacer chain and high hydrophilicity that result in a strong etching effect and a better dentin wettability but also a relatively low chemical bonding potential to hydroxyapatite compared to other self-adhesive monomers [26].…”
Section: Discussionmentioning
confidence: 99%
“…New self-adhesive flowable resin composites, such as Constic (C) (DMG, Germany) and Fusio Liquid Dentin (FLD) (Pentron Clinical, USA) were recently introduced to the dental market (10). The use of these materials eliminates the need for a separate bonding procedure, improves the ease of use and saves time (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study (14) reported a self-adhesive composite to be adequate for the repair of noncarious amalgam defects, in terms of microleakage. Moreover, studies have focused on the bonding strength of self-adhesive flowable resin composites to dentin, enamel, nano-composites or ceramics (10,(15)(16)(17)(18)(19)(20); however, information on the ability of these composites to bond with amalgam remains lacking.…”
Section: Introductionmentioning
confidence: 99%